Créer des formes, inventer des faires - Fabienne Wateau (Ateliers d'Anthropologie)
This text revisits several writings that grew out of my research. Their forms were chosen to render certain anthropological themes in a different format, by exploring their effects, by intending them for certain uses or audiences, by questioning them to bring out possible heuristic avenues. I will discuss the following: my theatrical play that served as a research tool, based on verbatim statements made by my interlocutors, published in On ne badine pas avec le progrès (2016)—a six-minute image montage is attached to it; an ongoing mixed-technique project, based on photograph colourisation linked with words extracted from the field, presented with some initial colour plates; and a retrospective examination of experimental screenings of two films in November 2022. Between forms and ways of doing, it will be a matter of exploring that “plastic relationship, that constant back-and-forth between the form and content” of scientific knowledge, as well as the combination of possibilities.